2009
DOI: 10.1186/1471-2431-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone growth during rapamycin therapy in young rats

Abstract: Background: Rapamycin is an effective immunosuppressant widely used to maintain the renal allograft in pediatric patients. Linear growth may be adversely affected in young children since rapamycin has potent anti-proliferative and anti-angiogenic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 26 publications
4
42
0
2
Order By: Relevance
“…In spite of the methodological limitations resulting from the retrospective data collection and the relatively small number of patients included in the analysis, our study suggests that SRL has the potential to adversely affect the growth of these patients, at least during the first 2 years of treatment with SRL. This finding is in agreement with experimental studies showing that administration of pharmacological doses of SRL decreased the longitudinal growth rate in young rats due to mechanisms likely dependent on the inhibitory effects of SRL on cell proliferation and VEGF expression at long bone growth plate [12][13][14]. This deleterious effect on longitudinal growth was evident, in our study, by the lower growth velocity and the reduced increment in height SDS found in children treated with SRL in comparison to children not receiving this drug.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In spite of the methodological limitations resulting from the retrospective data collection and the relatively small number of patients included in the analysis, our study suggests that SRL has the potential to adversely affect the growth of these patients, at least during the first 2 years of treatment with SRL. This finding is in agreement with experimental studies showing that administration of pharmacological doses of SRL decreased the longitudinal growth rate in young rats due to mechanisms likely dependent on the inhibitory effects of SRL on cell proliferation and VEGF expression at long bone growth plate [12][13][14]. This deleterious effect on longitudinal growth was evident, in our study, by the lower growth velocity and the reduced increment in height SDS found in children treated with SRL in comparison to children not receiving this drug.…”
Section: Discussionsupporting
confidence: 94%
“…However, experimental findings indicate that administration of SRL to fast-growing rats impairs longitudinal growth and induces marked alterations in growth-plate structure by mechanisms likely related to its inhibitory effects on cell proliferation and VEGF local expression [12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…However, she presented linear growth failure later on. Although mild CKD and steroids could contribute to the observed delayed growth, we hypothesize SRL to be the main deleterious factor in her growth, as has been demonstrated in growing rats [5,8]. rhGH allowed our patient's growth to catch up; her stature increased by ∼9 cm/year, as reported [16], normalizing her height, despite mild renal dysfunction and treatment with SRL [17].…”
Section: Discussionmentioning
confidence: 68%
“…When given to young rats, SRL significantly decreased endochondral bone growth too [8]. Despite the fact that linear growth may be adversely affected in young children, little is known about the effects of SRL on growing children.…”
Section: Introductionmentioning
confidence: 95%
“…(25) and decreased endochondral bone growth (26). A girl was described that stopped growing after switch from CsA to Sirolimus in one case report (27).…”
Section: We Recognized Problems With Wound Healing In Two Children Wmentioning
confidence: 99%